2021
DOI: 10.1556/066.2020.00204
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of edible Asparagus acutifolius and Asparagus officinalis collected from North Iraq and Turkey (Hatay)

Abstract: In this study, antioxidant, oxidant, antimicrobial, and antiproliferative activities of Asparagus acutifolius L. and Asparagus officinalis L., known for their nutritional properties, were determined. In this context, methanol (MeOH) and dichloromethane (DCM) extracts of plants were obtained. Total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) were determined using Rel Assay kits. Antimicrobial activities of plant extracts were determined against the test microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
(19 reference statements)
0
20
0
1
Order By: Relevance
“…Wild fruits are important in terms of the nutrients they contain, especially antioxidants. Recently, due to the increasing interest in natural nutrition, the trend towards edible wild fruits, which are seen as a source of bioactive components, has increased (Mohammed et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Wild fruits are important in terms of the nutrients they contain, especially antioxidants. Recently, due to the increasing interest in natural nutrition, the trend towards edible wild fruits, which are seen as a source of bioactive components, has increased (Mohammed et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Plants in particular have been used by humans for different purposes such as the treatment of diseases, nutrition, shelter, defense and warming, and they are still being used. In recent years, many researchers have reported that different plant species have different biological activities such as antioxidant, antimicrobial, anticancer, antiproliferative, anti-inflammatory, DNA preservative, anti-aging, antidepressant, antiallergic, hypoglycemic (Hu et al, 2017;Ayoub et al, 2018;Khan et al, 2018;Lichota and Gwozdzinski, 2018;Miastkowska and Sikora, 2018;Ribeiro et al, 2018;Salehi et al, 2019;Guo et al, 2020;Salehi et al, 2020;Mohammed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So, for diabetes management, alternative medicine is required to control this disorder. Plants are important natural materials that are used for treatment of many diseases (Sevindik et al, 2017;Mohammed et al, 2020Mohammed et al, , 2021. Islam is a religion of the ideal complete code of life.…”
Section: Introductionmentioning
confidence: 99%